2021
DOI: 10.1111/echo.15175
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between echocardiographic tricuspid annular plane systolic excursion and mortality in COVID‐19 patients: A Meta‐analysis

Abstract: Background:The evaluation of the tricuspid annular plane systolic excursion (TAPSE) is recommended to assess the right ventricular (RV) systolic function. We performed an updated meta-analysis of the association between TAPSE and short-term mortality in COVID-19 patients. Methods: MEDLINE and Scopus databases were searched to locate all the articles published up to May 1, 2021, reporting data on TAPSE among COVID-19 survivors and non-survivors. The difference of TAPSE between the two groups was expressed as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Previous studies have demonstrated the clinical utility of cardiac and lung POCUS for triage, diagnosis, and management of patients with COVID‐19 13–14 . Other studies also showed high rates of cardiac and pulmonary abnormalities, as well as the ability to predict a worse outcome in this group of patients 1,2,15,16 . However, most of these studies were performed with full‐size standard ultrasound machines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the clinical utility of cardiac and lung POCUS for triage, diagnosis, and management of patients with COVID‐19 13–14 . Other studies also showed high rates of cardiac and pulmonary abnormalities, as well as the ability to predict a worse outcome in this group of patients 1,2,15,16 . However, most of these studies were performed with full‐size standard ultrasound machines.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14] Other studies also showed high rates of cardiac and pulmonary abnormalities, as well as the ability to predict a worse outcome in this group of patients. 1,2,15,16 However, most of these studies were performed with full-size standard ultrasound machines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decreased TAPSE (<17 mm) was found in three (8.6%) moderate and five (35.7%) critically-severe patients [12]. The American Society of Echocardiography recommends routinely using (TAPSE) to evaluate the RV systolic function; a low TAPSE value may be considered an earlier manifestation of cardiac involvement or complications in COVID-19 patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The adverse effect of COVID-19 on the RV is unsurprising as prior studies revealed RV dilation or dysfunction are the most common echocardiographic findings in those with acute respiratory distress syndrome (ARDS) 6,7 and RV dysfunction is associated with mortality in ARDS. 8 While substantial evidence suggests that RV dysfunction is associated with in-hospital mortality in acute COVID-19, [9][10][11] the prognostic implications of RV dilation alone are less clear. While some studies have found an association between RV dilation and mortality 12,13 , others have not.…”
Section: Introductionmentioning
confidence: 99%